Mechanical behavior of unidirectional composites with hexagonal and uneven distribution of fibers in the transverse cross-section. (September 2018) - Muthukumar, M; Prasath, J; Desai, YM; Naik, NK
Uneven distribution of fibers can adversely affect the mechanical behavior of unidirectional composites. A micromechanical model based on finite element analysis is presented to evaluate elastic and strength properties of such composites under normal loading. Analysis starts with identification of micro unit cells/micro repetitive unit cells and/or representative volume elements. Because of uneven distribution/random distribution of the fibers, fiber volume fraction can be different for different micro unit cells present at different locations in the transverse cross-section of the unidirectional composite. Configuration of the micro unit cell is worked out at the outset considering the fiber distribution having the hexagonal arrangement, but with different volume fraction at different locations. For such micro unit cells, elastic and strength properties are obtained based on finite element analysis starting with the elastic and strength properties of fiber and matrix. With the properties obtained for different micro unit cells, elastic and strength properties of the unidirectional composite with micro unit cells having hexagonal arrangement of fibers with different volume fraction at different locations in the transverse cross-section are determined. Further, elastic and strength properties are evaluated for micro unit cells with uneven distribution of fibers in the transverse cross-section.